Pelatihan Manajemen Usaha Untuk Meningkatkan Pengelolaan Usaha Mikro Kecil Menengah - Deri, Rahmi Rismayani; Nur, Siti; Fatman, Yenni; Amelia, Eka (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Micro, Small, and Medium Enterprises (MSMEs) in Dampit Village are well-established with qualified business management knowledge. Business management training in Dampit Village aims to increase MSMEs' productivity, quality, and development. Training on human resources is one of the efforts to develop human resources in a planned manner to increase knowledge and skills, especially in a job that can achieve the goals of an organization/company. The training uses lesson studies which are divided into several stages of implementation; the first stage is planning, the second stage is implementation, and the third stage is reflection. The participants seemed to be very enthusiastic due to the existence of this training, as can be seen from the number of participants who attended and were active in this training activity. The result of this training explained that participants were happy to take part in this training, the material provided was easy to understand and could improve their skills. This shows that each participant has mastered the training.